Human action recognition in the dark based on transferring learning and LSTM - Yang, Fan (Nanyang Technological University, 2023)
Today, information technology is pervasive worldwide. Throughout the years, it has undergone continuous transformation and will continue to evolve. From the initial invention of the computer to the development of software and artificial intelligence, a new era in human life has been unveiled.